Ruth Bader Ginsburg’s Equal Protection Clause: 1970-80 - Williams, Wendy W. (Columbia Journal of Gender and Law, 2012)
Professor Ruth Bader Ginsburg of Columbia Law School was the leading Supreme Court litigator for gender equality in the crucial decade, 1970-80. In addition to teaching her classes, producing academic articles, and co-authoring the first casebook on sex discrimination and the law, she worked on some sixty cases (depending on how one counts), including over two dozen cases in the Supreme Court. Rumor has it she did not sleep for ten years; her prodigious output gives the rumor some credence.’ Her impact on the law during that critical decade earned her the title “the Thurgood Marshall of the women’s movement” and secured her place in history-even before she became a federal appellate judge and Supreme Court justice. I will devote my allotted space to two, intimately intertwined, topics: first, Ruth Ginsburg and the Supreme Court’s standard of review in sex discrimination cases, and second, the substance of Ruth Ginsburg’s concept of gender equality in law.